1993
DOI: 10.1177/039139889301600303
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alpha-1-Antitrypsin in Hemodialysis Patients with Dialysis Arthropathy

Abstract: Dialysis arthropathy is the most prominent dialysis-related amyloidosis feature. Alpha-1-antitrypsin (alpha-1-proteinase inhibitor) is the major circulating antiprotease. Twenty-three otherwise uncomplicated hemodialysis patients with well-documented dialysis arthropathy had a significantly (p < 0.05) lower serum mean concentration, 1,960 +/- 410.4 mg/l of alpha-1-antitrypsin than 47 patients with no joint symptoms who had a mean concentration of 2,256.6 +/- 424.5 mg/l. Decreased levels of the substance were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…No effect of either disease or dialysis was seen in these patients. Similar results have been reported by Docci et al [4] who reported lower mean serum alpha-1 AT in 23 uncomplicated haemodialysis patients. Group B had 20% patients in whom a normal predialysis level culminated into an elevated abnormal level.…”
Section: Discussionsupporting
confidence: 90%
“…No effect of either disease or dialysis was seen in these patients. Similar results have been reported by Docci et al [4] who reported lower mean serum alpha-1 AT in 23 uncomplicated haemodialysis patients. Group B had 20% patients in whom a normal predialysis level culminated into an elevated abnormal level.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, reagent‐grade bovine fibrinogen and thrombin were purchased commercially and combined with ovine fibronectin and vitronectin extracts isolated by preparative affinity chromatography. This single‐step enrichment increases fibronectin and vitronectin concentrations approximately 10‐fold relative to serum, but substantial amounts of other, uncharacterized serum proteins are also present in the concentrates and may contribute beneficial anti‐protease and mitogenic effects20, 21. For example, the improved hydrogel integrity observed in samples containing these extracts is likely due to anti‐proteases, such as α‐2 macroglobulin, and residual serum transglutaminase within the glycoprotein extracts, and not to any direct effects of either fibronectin or vitronectin on crosslinking or degradation.…”
Section: Discussionmentioning
confidence: 99%